Influence of age on cognition and scopolamine induced memory impairment in rats measured in the radial maze paradigm - Appenroth, Dorothea; Fleck, Christian (Arzneimittelforschung, 2010)
The influence of age on (1) cognition and (2) scopolamine (CAS 51-34-3) induced memory impairment in female rats was measured in the radial maze paradigm (RAM).(1) First training trials were done with3 and 12 months old rats. Rats were trained to find all eight food baits in the RAM without errors and within 1 min. Both 3- and 12-month old rats need about 15 trials for the first-time learning of the RAM task. After intervals of 3 and6 months, respectively, initially young rats were re-trained with an age of 6 and12 months. Surprisingly, re-trained rats successfully completed the maze runs already after one re-training trial. Thus the phenomenon of preserved spatial memory was approved for female rats.(2) Memory impairment by scopolamine in the RAM was tested for the first time in rats with an age of 3 months.After a control run, the rats received an i. p. injection of either scopolamine hydrochloride (0.05 mg/100 g b. wt.) or saline vehicle. The effect of scopolamine on working memory was measured 20 min after administration. Training procedure and scopolamine administration were repeated at an age of 6, 12, 18, and 24 months in the same manner. The cognition impairment after scopolamine (number of errors: control: ≤ 1; scopolamine: 5–6) remains constant between 3 and 24 months of age. The only significant difference was the increase in run time in rats older than 18 months caused by degenerative changes developing with age.It can be concluded that the drug effect on cognition and working memory can be measured in young and old-aged female rats with the same results.
Keywords: Age; Alzheimer’s disease; CAS 51-34-3; Memory; Radial maze; Scopolamine; Rat